Historical shocks and persistence of economic activity: Evidence from a unique natural experiment - Michael Fritsch; Alina Sorgner; Michael Wyrwich; Evguenii Zazdravnykh (Friedrich Schiller University Jena, 2016)
This paper investigates the persistence of entrepreneurship in the region of Kaliningrad between 1925 and 2010. During this time period the area experienced a number of extremely disruptive shocks including; devastation caused by World War II, a nearly complete replacement of the native German population by Soviets, and 45 years under an anti- entrepreneurial socialist economic regime followed by a shock-type transition to a market economy. Nevertheless, we find a surprisingly high level of persistence of industry-specific self-employment rates in the districts of the Kaliningrad region. Our analysis suggests that persistence of entrepreneurship is higher in regions with a history of successful entrepreneurship. That is, in regions where a specific industry was particularly efficient and entrepreneurial activity was especially pronounced.
Keywords: L26; N94; P25; P5; 330; entrepreneurship; regional culture; persistence